Hunger-induced convergence of personality traits towards ambush-predatory behavior in ball pythons (Python regius, Shaw 1802) - Octavian CRAIOVEANU; Elisabeth SPATARO; Cristina CRAIOVEANU (Studia Universitatis Babeș-Bolyai. Biologia)
Personality traits have been shown to be influenced by environmental and internal factors, hunger being one of the most important. The resulting behavior fluctuates greatly depending on the feeding ecology of the different species and intraspecific individual variation.